ACCORDING TO THE CAUSES OF THE EARTHQUAKE TYPES - Ismoilov Jaloliddin (Journal of new century innovations, 2022)
Annotatsion: This article is devoted to the topic of earthquakes and their causes. The article provides information on the hypocenter, epicenter, the epicenter of an earthquake, earthquake strength, seismic scale and the most common seismic scales in the world, as well as seismic and seismic regions, types of earthquakes and tsunamis.